“This Is a Food Ad but It Is Presenting Gender Stereotypes!”: Practicing Critical Language Awareness in an Iranian EFL Context - Seyyedeh Fahimeh Parsaiyan (Journal of English Language Teaching and Learning, 2019)
Despite a fairly long emergence of critical approaches to language teaching, there still seems to be a dearth of practitioner inquiries narrating experiences of implementing Critical Language Awareness (CLA) in English as Foreign Language (EFL) contexts. Prompted, the present study narrates the measures taken by an Iranian language teacher for encouraging learners to analyze and examine language deployment in the world around them. The participants of this semester-long study were a community of twenty young female students studying English Literature at a state university in Tehran, Iran who were engaged in a series of reading events including reflective reading of advertisements and TV commercials, and critical analysis of literary works, news and journalistic writings, inter alia. The analysis of classroom records plus reflective journals written by the students display the ways through which the students practiced standing back from texts, questioning the biased ideas, developing reasoned position, and responding in their own voices.